Aided Hearing Moderates the Academic Outcomes of Children with Mild to Severe Hearing Loss - Tomblin, J. Bruce (Ear Hear, 2020)
OBJECTIVES: There are very limited data regarding the spoken language and academic outcomes of children with mild to severe hearing loss during the elementary school years and the findings of these studies are inconsistent. None of these studies have examined the possible role of aided hearing in these outcomes. This study used a large cohort of children to examine these outcomes and in particular to examine whether aided hearing moderates the effect of hearing loss with regard to these outcomes. DESIGN: The spoken language, reading, writing, and calculation abilities were measured after second and fourth grades in children with mild to severe hearing loss (children who are hard of hearing; CHH, n = 183) and a group of children with normal hearing (CNH, n = 91) after the completion of second and fourth grades. Also, among the CHH who wore hearing aids, aided better-ear speech intelligibility index (BESII) values at the age of school entry were obtained. RESULTS: Oral language abilities of the CHH with mild and moderate hearing loss were similar to the CNH at each grade. Children with moderately-severe hearing loss (better-ear pure tone threshold > 59 <76 dB HL) had significantly poorer oral language and reading skills than the CNH at each grade. The children with mild and moderate hearing loss did not differ from the CNH in oral language or reading. No differences were found between the CHH regardless of severity and CNH with regard to spelling, passage writing, or calculation. The degree to which hearing aids provided audible speech information played a moderating role in the oral language outcomes of CHH and this moderation of language mediated the relationship between the unaided hearing ability of the CHH and their academic outcomes. CONCLUSIONS: As a group, children with mild and moderate hearing loss have good outcomes with regard to language and academic performance. Children with moderately-severe losses were less skilled in language and reading than the CNH and CHH children with mild and moderate losses. Audibility provided by hearing aids was found to moderate the effects of hearing loss with respect to these outcomes. These findings emphasize the importance of including the effects of clinical interventions such as aided hearing when examining outcomes of CHH.